Óleos e extratos vegetais no controle da ferrugem asiática da soja (Glycine max (L.) Merril.) - Borges, Daniella Ines (2007)
The current agriculture has increased its potential of production, as result of the application of chemical products for the control of plagues and disease of plants and this has caused serious damages to the environment and to the health of the agriculturist. The exploration of the biological activity of secondary composites of plants can consist in an additional potential form of alternative control, thus reducing the ambient impact. Therefore, this work aimed select vegetal extracts and essential oils, for the control of the Asian soybean rust of the soy. First of all, test in vitro were carried out with with 61 vegetal extracts and 5 essential oils, to evaluate the effect of these in the germination of urediniospores of P. pachyrhizi, being the extracts obteined of prudent Tília cordata, Pelargonium sp., Lavandula officinalis and Mentha pulegium selected for the tests in vivo. In green house, these extracts were sprayed in soybean plants, with different levels of resistance, in order to evaluate the effect in severity and production of uredinia sores, caused by the attack of fungus. Amongst the itens evaluated, the treatments and the interaction cultivar x treatments had not presented significant effect, only the variable cultivate, where the PI 459025, with resistence gene Rpp4, was distinguished, presenting the best resultes when compared with the others. In the evaluation of the number of uredinia significant differences had been observed, being that the extracts of Pelargonium sp. e L. officinalis had presented statistically similar resultes to the treatment with fungicide. In addition, the same extracts used in the test at the green house, were evaluated through Scanning Electron Microscopy, in leaves detached of the cultivar MG/BR 46 of the genotype PI 230970, with a gene of resistance Rpp2. The eletromicrographs done had shown differences in the form and sizes of esporos and appressoria, being this considered a characteristic of the fungus. Concerning the effect of the extracts, no deformity was found, only for the genotype PI 230970, the formation of the appressoria was delayed. For all the treatments, had been observed spores germinating and later on the formation of the appressoria, except at the treatment with fungicide, where the majority of the spores did not germinate. This indicates a possible way of performance of the extracts after-penetration of the fungus.